English Vocabulary Learning Strategies of non-English major university students - Alpino Susanto, Fazlina Ab Halim, Berhannudian Mohd Salleh (International Conference on Industrial Revolution for Polytechnic Education, 2019)
This study aims to examine vocabulary learning strategies among university students in Indonesian context. The current state of the art of vocabulary learning strategies (VLSs) in Indonesia is typified by lack of attention in students’ practicality. So, there is urgent need for theoretical research to enhance the precision of conception of strategies overview the students’ level of the strategies. There were 314 students from Universities in Batam-Indonesia, participated in this study. The research is tended for a quantitative research into Non-English Majors’ preference for vocabulary learning strategies. The vocabulary learning strategies questionnaire was adopted and adapted from a previous study. The researchers translated the questionnaire from English into Indonesian. The validity of the questionnaire was ascertained by language experts. A pilot study was conducted to verify the reliability of the questionnaire by using the Winstep version 3.73. SPSS software was used to assess the mean score of the indicators of vocabulary learning strategies. The data of the vocabulary learning strategies is elicited from survey by validated questionnaire. Based on the result this paper suggests that Non-English majors should manage to grasp more useful vocabulary learning strategies and then make appropriate adjustments to improve their vocabulary learning. As for teachers and lecturer, they should help language learners to build positive strategy training into English classes and encourage students to systematize their own learning strategies instead of using these strategies unsystematically.